2014
DOI: 10.1039/c3dt52011k
|View full text |Cite
|
Sign up to set email alerts
|

Investigations into variations in local cationic environment in layered oxide series InGaO3(ZnO)m(m = 1–4)

Abstract: Layered oxides of the series InGaO3(ZnO)m (m = 1-4) are interesting due to their structural anisotropy. Here, we report a comprehensive study of their structural details, focusing on the local cationic environment in bulk powder samples by MASNMR and EXAFS, which is hitherto not attempted. It is found that the Ga geometry varies gradually from pure pentacoordinated to a mixture of penta and tetracoordinated with increasing amounts of tetracoordination as we move across the series, contrary to previous reports … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…The differences in the structural accommodation of M 3+ (M = In, Ga, and Al) might be influenced by changes in the coordination geometries. Previous studies on Zn k InGaO k+3 show that Ga 3+ could be occupying a BPT or a Td coordination; 17,18 however, no information about coordination states of Al 3+ in these phases has been reported. In order to clarify this question, we have employed MAS NMR, which is a powerful tool to understand the local environments of magnetically active nuclei.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The differences in the structural accommodation of M 3+ (M = In, Ga, and Al) might be influenced by changes in the coordination geometries. Previous studies on Zn k InGaO k+3 show that Ga 3+ could be occupying a BPT or a Td coordination; 17,18 however, no information about coordination states of Al 3+ in these phases has been reported. In order to clarify this question, we have employed MAS NMR, which is a powerful tool to understand the local environments of magnetically active nuclei.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…In this sense, Keller et al, 17 from single crystal X-ray diffraction and convergent beam electron diffraction (CBED) on Zn 4 InGaO 7 , found that Ga 3+ ions are in trigonal bipyramidal (TBP) sites in the wurtzite block, forming an equatorial plane at half distance between the InO 6 octahedral layers to promote the inversion of the wurtzite structure. Narendranath et al 18 using Magic Angle Spinning Solid State Nuclear Magnetic Resonance (MAS NMR) of 71 Ga and EXAFS, reported that Ga/Zn-O wurtzite blocks are formed by outer strata of ZnO and an inner layer of Ga-O/Zn-O. According to their results, when k increases the Ga 3+ coordination shifts from TBP to tetrahedral, probably because Ga 2 O 3 has solubilized in ZnO (especially at high k values), and hence, has a wurtzite type structure with corner sharing tetrahedra.…”
mentioning
confidence: 99%
“…If the syntheses are performed under air in an open environment, the process always leads to the presence of secondary phases due to the unavoidable losses of the most volatile elements (mostly Zn as ZnO has the largest partial pressure at high temperature). The amount of secondary phases is all the more significant that the integer m becomes larger, when the relative fraction of Zn in the compounds increases, being known also that the reaction rate gets slower when m increases . To improve the quality of the samples by minimizing the volatilization, two main solutions have been followed in the past, namely the use during the sintering of the pellets of a sacrificial powder of the same stoichiometry, or the use of sealed platinum crucibles .…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4] In this structure, octahedral-coordinated In atoms form an [InO 2 ] − layer, whereas Zn and Ga atoms occupy distorted tetrahedra and bipyramids and form a [GaZn m O m+1 ] + layer, with a distribution of Zn and Ga that is still under debate and may depend on the value of m (see for example Ref. [5][6][7][8]). To date, outside their crystallographic properties, they have been mostly studied in the thin film form.…”
Section: Introductionmentioning
confidence: 99%
“…After treatments between 350°C and 800°C, beside Ga VI , both Ga IV and Ga V were identified. The penta-coordination of gallium in oxide glasses and ceramics was reported in few studies, [25][26][27][28][29][30] but only one gallium compound with exclusively penta-coordinated gallium was mentioned. 26 Our current investigation points out that the heat-treatment temperature enhancement to 850°C already leads to 95.3% Ga V , and after 900°C treatment exclusively penta-coordinated gallium is evidenced (Table III).…”
Section: Resultsmentioning
confidence: 99%